Unique Footprint in the scl1.3 Locus Affects Adhesion and Biofilm Formation of the Invasive M3-Type Group A Streptococcus - Bachert, Beth A.; Choi, Soo J.; LaSala, Paul R.; Harper, Tiffany I.; McNitt, Dudley H.; Boehm, Dylan T.; Caswell, Clayton C.; Ciborowski, Pawel; Keene, Douglas R.; Flores, Anthony R.; Musser, James M.; Squeglia, Flavia; et al. (Frontiers in Cellular and Infection Microbiology, 2016)
The streptococcal collagen-like proteins 1 and 2 (Scl1 and Scl2) are major surface adhesins that are ubiquitous among group A Streptococcus (GAS). Invasive M3-type strains, however, have evolved two unique conserved features in the scl1 locus: (i) an IS1548 element insertion in the scl1 promoter region and (ii) a nonsense mutation within the scl1 coding sequence. The scl1 transcript is drastically reduced in M3-type GAS, contrasting with a high transcription level of scl1 allele in invasive M1-type GAS. This leads to a lack of Scl1 expression in M3 strains. In contrast, while scl2 transcription and Scl2 production are elevated in M3 strains, M1 GAS lack Scl2 surface expression. M3-type strains were shown to have reduced biofilm formation on inanimate surfaces coated with cellular fibronectin and laminin, and in human skin equivalents. Repair of the nonsense mutation and restoration of Scl1 expression on M3-GAS cells, restores biofilm formation on cellular fibronectin and laminin coatings. Inactivation of scl1 in biofilm-capable M28 and M41 strains results in larger skin lesions in a mouse model, indicating that lack of Scl1 adhesin promotes bacterial spread over localized infection. These studies suggest the uniquely evolved scl1 locus in the M3-type strains, which prevents surface expression of the major Scl1 adhesin, contributed to the emergence of the invasive M3-type strains. Furthermore these studies provide insight into the molecular mechanisms mediating colonization, biofilm formation, and pathogenesis of group A streptococci.